Optimization of the Electrocatalytic Activity of Mn4- Macrocyclics Adsorbed on Graphite Electrodes for the Electrochemical Oxidation of L-Cysteine by Tuning the M (Ii)/(I) Formal Potential of the Catalyst: An Overview - Zagal-Moya, J; Zagal-Moya, J; Recio-Cortes, F; Recio-Cortes, F; Venegas-Toledo, R (Elsevier Ltd, 2014)
The M(II)/(I) formal potential of MN4 macrocyclic complexes dictates their electrocatalytic activity for many reactions and L-cysteine oxidation is not an exception. In this work we review the literature related to this reaction and propose a semi-empirical model that can describe the catalytic activity of these chelates in terms of their formal potential. A correlation of log i (at constant potential) versus the M(II)/(I) formal potential for M= Fe,Co) of the catalysts gives a volcano curve. Our results clearly show that the M (II)/(I) formal potential of N4-macrocyclic complexes needs to be adjusted to values around -1.0 V vs. SCE to obtain the highest catalytic activity for the oxidation of L-cysteine. When comparing chelates of different metals (M= Cr, Mn, Fe, Co) of tetrasulphonated phthalocyanines only a linear correlation is obtained. © 2014 Elsevier Ltd.